Therapeutic effects of rifampin and erythromycin in experimental murine brucellosis - Felek, S; Demirdag, K; Kalkan, A; Akbulut, A (Blackwell Science Ltd, 2000)
[Abstract Not Available]
Keywords: Doxycycline; Azithromycin; Efficacy